Development of Smart Apps Creator (SAC)-Based Android Application Learning Media to Improve Students' Understanding of Islamic Education Materials in Elementary Schools - Ani Nur Aeni; Nurdinah Hanifah; Rahimah Rahimah; Ahmad Arifuddin (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThis research is motivated by the importance of creating digital learning media, considering that the learning that is currently carried out is in the digital era. SAC is software to create applications without having to go through programming code. This research aims to create a SAC-based Android application learning media product to improve students' understanding of Islamic education materials in elementary schools. The research method used is R&D, with 4D design (define, design, development, and disseminate). The findings are: The learning media for the andorid application with SCA is called the SAHIH application, an abbreviation for “Sahabat Fikih” (Friends of Fiqh). The SAHIH application is a SAC-based android learning media made for materials to welcome puberty in grade IV of elementary school. The SAHIH application is made based on the analysis of needs and analysis of independent curriculum documents. This app has been validated by media experts and material experts with very decent grades. The SAHIH application has gone through a limited, extensive trial stage and has received a very good and very feasible assessment, it has also been tested for its effectiveness. Thus, it can be concluded that the SAHIH application can be applied to Islamic education.Keywords: smart apps creator, android application, learning media, islamic education, elementary school.AbstrakPenelitian ini dilatarbelakangi oleh pentingnya membuat media pembelajaran digital, mengingat pembelajaran yang dilakukan saat ini berada di era digital. SAC adalah perangkat lunak untuk membuat aplikasi tanpa harus melalui kode pemrograman. Penelitian ini bertujuan untuk menghasilkan produk media pembelajaran aplikasi android berbasis SAC untuk meningkatkan pemahaman siswa tentang materi PAI di sekolah dasar. Metode penelitian yang digunakan adalah R&D, dengan desain 4D (define, design, develop, dan diseminasikan). Temuannya adalah: Media pembelajaran untuk aplikasi andorid berbasis SCA ini diberi nama aplikasi SAHIH, singkatan dari